Corrosion and mechanical behavior of plasma nitrated metallic biomaterial surfaces. (2021) - Venkatesan, S.P.; Jeevahan, Jeya; Purusothaman, M.; Venkatesh, S.; Rakesh Vimal, M.
Abstract: Biomaterials are the materials that are used to replace a biological tissue or support the system. The most commonly used metal SS316L and another metal Ti6Al4V which has the desired properties selected for improving their feasibility. SS316L and Ti6AL4V though being highly resistant to corrosion, show corrosive properties while used in a biological system. So, they need to be made much compatible while using it as a biomaterial thus plasma nitriding is done and the rate of corrosion is reduced making it much more compactable as a biomaterial. Plasma nitriding is a heat treatment process that diffuses nitrogen ions through the surface i.e. form nitrides and reducing the reactivity and thus improving the corrosion resistance. These metals are nitrided for different periods of 8 h and 24 h separately and the changes in the properties are studied using various tests. An electrochemical corrosion test is done to calculate corrosion rates. SEM and EDAX are done to study the structural topography and composition respectively. Vickers hardness test is done to show the effect of plasma nitriding on the hardness of the metals. On studying all the test results the better metal suitable as a biomaterial is determined.